MEMBOYONG KEPENTINGAN PRIBADI MENUJU KEUTAMAAN SOSIOLOGIS - Herwindo Chandra (STIKAS Santo Yohanes Salib Kalimantan Barat, 2019)
Self-interest starts at the early life of human beings. Along with his body self-interests also grows in the biological growth of a child. Mankind tends to do everything for his own interest, such as to fulfill his needs. Meanwhile, there is another terminology that close to self-interest, i.e. selfishness. Regardless we have to determine the meaning of both terminologies. Self-interest depends on condition, while selfishness focus on ones own interest. Selfishness has no value per se, and it is different with self-interest. In social relationship, self-interest is not without problem. In this paper, we try to describe several conditions of such relationship by using the theory of George Simmel. Is there any condition to bring the self-interest for a good relationship? Therefore, the purpose of this paper is to achieve the knowledge and an encouragement for the highest social virtue in relationship.